Factors influencing university brand image: A case study at a university in Vietnam - Sen, Cao Thi; Dinh, Nguyen Van (Edelweiss Applied Science and Technology, 2025)
This study aims to identify the factors affecting the brand image of Nam Can Tho University and, on that basis, propose some policy implications to enhance the university’s brand image. The study employs a combination of qualitative and quantitative research methods. Qualitative research aims to determine the research model and calibrate the scale. The research model consists of four independent variables: brand association, brand awareness, brand loyalty, and perceived quality, which impact the brand image of Nam Can Tho University. The analysis results from a survey of 240 students, conducted through steps such as reliability testing of the measurement scale using Cronbach’s Alpha, exploratory factor analysis, correlation analysis, and multiple linear regression analysis, show that the brand image is influenced by four factors: perceived quality, association, brand awareness, and brand loyalty. Based on the research findings, policy implications are proposed to enhance the brand image of Nam Can Tho University.